Influence of Toothbrush Abrasion and Surface Treatments on Roughness and Gloss of Polymer-Infiltrated Ceramics - Nawaf Labban (MDPI AG, 2021)
The aim of this study was to compare the surface roughness and gloss of polymer-infiltrated ceramics after simulated in vitro toothbrushing in different storage mediums. Four polymer- infiltrated ceramics were evaluated, Lava ultimate (LU), Vita enamic (EN), Shofu (SH), and Crystal ultra (CU). The control group was a feldspathic ceramic, Vita Mark II (VM). One hundred and twenty specimens (12 × 14 × 2.5 mm) were prepared using a precision saw. For each material (n = 24), the specimens were allocated into two groups, polished and stained. The specimens of each group were stored (for 7 days) in either citric acid (0.2N) or distilled water. Data for surface gloss (ΔE*SCE-SCI) and roughness (Ra) were evaluated before (baseline) and after simulated toothbrushing. For toothbrushing simulation, a toothpaste slurry containing a toothpaste of 100 relative dentin abrasion (RDA) and 0.3 ml distilled water was used for 3650 cycles (7300 strokes) for each specimen. Data were analyzed using t-test and ANOVA. A p-value of ≤ to 0.05 was considered significant. The highest mean value of surface gloss was identified in CU (stained—water) (4.3 (0.47)) (ΔE*) and EN (stained—acid) (4.3 (1.00)) (ΔE*) specimens, whereas the lowest mean value was shown by SH (stained—acid) (2.04 (0.42)) (ΔE*) samples. The highest mean value of surface roughness was observed in SH (0.40 (0.99)) Ra (stained—acid) whereas the lowest in VM (0.13 (0.039)) Ra (polished— water). A significant difference (p < 0.05) was observed in surface roughness and gloss between the materials with simulated toothbrushing, except in VM and LU, respectively. Therefore, it can be concluded that simulated toothbrushing impacts on surface roughness and gloss, irrespective of the storage medium.